2014
DOI: 10.1186/s12911-014-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

The design of a low literacy decision aid about rheumatoid arthritis medications developed in three languages for use during the clinical encounter

Abstract: BackgroundShared decision-making in rheumatoid arthritis (RA) care is a priority among policy makers, clinicians and patients both nationally and internationally. Demands on patients to have basic knowledge of RA, treatment options, and details of risk and benefit when making medication decisions with clinicians can be overwhelming, especially for those with limited literacy or limited English language proficiency. The objective of this study is to describe the development of a medication choice decision aid f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
(31 reference statements)
0
31
0
Order By: Relevance
“…RA Choice was created to facilitate conversation between patients and clinicians about RA medications (13) and support SDM with patients who experienced an inadequate response to methotrexate monotherapy. Developed in three languages, the tools are aimed at populations with barriers to communication.…”
mentioning
confidence: 99%
“…RA Choice was created to facilitate conversation between patients and clinicians about RA medications (13) and support SDM with patients who experienced an inadequate response to methotrexate monotherapy. Developed in three languages, the tools are aimed at populations with barriers to communication.…”
mentioning
confidence: 99%
“…It is important that culturally and linguistically fluent interpreters be used. 33,34 Providers who do not have that level of fluency should not use their own second-language skills, as is often done in clinical encounters. Additionally, it is not optimal to simply translate SDM clinical decision tools into other languages.…”
Section: Limited English Proficiencymentioning
confidence: 99%
“…Only one other PtDA includes all DMARD options and a clear plan for integration in daily clinical care. It consists of a card deck to be used during the medical encounter and is developed for patients with limited health literacy or limited English language proficiency (158).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PtDA's sometimes have a positive impact on patients' satisfaction with decision-making, anxiety, adherence or health outcomes (30). Although these effects are not likely to be very different, in rheumatology, only a few studies on PtDA's have been reported and their effects have not yet been thoroughly determined (30,66,158).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation